A Functional Variant Associated with Atrial Fibrillation Regulates PITX2c Expression through TFAP2a - Ye, Jiangchuan; Tucker, Nathan R; Weng, Lu-Chen; Clauss, Sebastian; Lubitz, Steven A; Ellinor, Patrick T (American journal of human genetics, 2016)
The most significantly associated genetic locus for atrial fibrillation (AF) is in chromosomal region 4q25, where four independent association signals have been identified. Although model-system studies suggest that altered PITX2c expression might underlie the association, the link between specific variants and the direction of effect on gene expression remains unknown for all four signals. In the present study, we analyzed the AF-associated region most proximal to PITX2 at 4q25. First, we identified candidate regulatory variants that might confer AF risk through a combination of mammalian conservation, DNase hypersensitivity, and histone modification from ENCODE and the Roadmap Epigenomics Project, as well as through in vivo analysis of enhancer activity in embryonic zebrafish. Within candidate regions, we then identified a single associated SNP, rs2595104, which displayed dramatically reduced enhancer activity with the AF risk allele. CRISPR-Cas9-mediated deletion of the rs2595104 region and editing of the rs2595104 risk allele in human stem-cell-derived cardiomyocytes resulted in diminished PITX2c expression in comparison to that of the non-risk allele. This differential activity was mediated by activating enhancer binding protein 2 alpha (TFAP2a), which bound robustly to the non-risk allele at rs2595104, but not to the risk allele, in cardiomyocytes. In sum, we found that the AF-associated SNP rs2595104 altered PITX2c expression via interaction with TFAP2a. Such a pathway could ultimately contribute to AF susceptibility at the PITX2 locus associated with AF.